Microalgae Cultivation Modes and Systems - Tan, H.L. (Nova Science Publishers, Inc., 2021)
Microalgae are photosynthetic microorganisms that can be found both in freshwater and marine systems. They can grow as individual cell or associated in chains or small colonies. Recently, microalgae cultivation has garnered huge research attention due to the enormous interest in the bioproduction of valuable and versatile metabolites. This chapter reviews different microalgae cultivation modes and systems, in which four prevalent microalgae cultivation modes, viz. photoautotrophic, heterotrophic, mixotrophic and photoheterotrophic cultivation modes are detailed. Photoautotrophic microalgae cultivation appears to be the most common mode, as the process is driven by the interest in greenhouse gas (CO2) capture and solar energy exploration. Nevertheless, artificial lights are often used to ensure optimum microalgae growth, which goes against the idea of green process. Heterotrophic cultivation is sought to be effective in promoting initial growth of microalgae with the usage of organic carbon sources. Mixotrophic cultivation combines the advantageous features of photoautotrophic and heterotrophic cultivation for higher biomass and lipid productivity, where wastewater would be a promising cultivation medium for this mode. Photoheterotrophic cultivation is the least recommended mode as it inflicts high contamination risk while increasing cultivation cost. In addition, four microalgae cultivation systems are also discussed in this chapter, such as batch, fed-batch, semi-continuous and continuous systems. Batch cultivation system is suitable for small-scale investigation for growth optimization of microalgae while fed batch, semi-continuous and continuous cultivations offer better control over sluggish lag phase and help to reduce contamination risk. More future works are needed to fully discover the potential of microalgae for various metabolites production in different microalgae cultivation modes and systems. Â© 2021 by Nova Science Publishers, Inc.